ANALISIS GENDER TERHADAP KEGIATAN PERIKANAN PANTAI: KASUS KABUPATEN SUBANG, JAWA BARAT (Gender Analysis of Coastal-Fisheries Activities: Case of Subang District, West Java Province) - Sri Murni Soenarno; Daniel R. Monintja; Rudy C. Tarumingkeng; Aida Vitayala S. Hubeis (Buletin PSP, 2007)
The Subang district is located in the north coast of Java Island. One of its economic sources is fisheries. Fifty percent of its production comes from sea. Women  have multiple roles in fisheries activities, such as trader, fish-processor, and financial administrator, but their roles are not documented. This research is aimed (1) to analyze whether the Subang District coastal-fisheries activities have been gender responsive, and (2) to make a coastal-fisheries action plans which is gender resporuive. The data analyses using Gender Analysis Pathway (GAP) and Moser Analysis. The results of  research show that (1) coastal-fisheries activities of Subang District have not yet gender  responsive, and (2) the action plans consist of capacity building, increasing education level, fostering community participaticm, improving local-based fisheries technology, and increasing employment opportunity.Key words: coastal-fisheries activities, gender, small-scale fishermen,